Integrating network pharmacology and experimental models to investigate the efficacy of QYHJ on pancreatic cancer. (28th October 2022) - Yang, Pei-wen; Xu, Pan-ling; Cheng, Chien-shan; Jiao, Ju-ying; Wu, Yuan; Dong, Shu; Xie, Jing; Zhu, Xiao-yan
Abstract: Ethnopharmacological relevance: The Qingyihuaji decoction (QYHJ) is composed of seven herbs: Scutellaria barbata D.Don (Banzhilian, HSB), Gynostemma pentaphyllum (Thunb.) Makino (Jiaogulan, GP), Oldenlandia diffusa (Willd.) Roxb. (Baihuasheshecao, HDH), Ganoderma lucidum (Leyss. ex Fr.) Karst . (Lingzhi, GL), Myristica fragrans Houtt . (Doukou, AK), and Amorphophallus kiusianus (Makino) Makino (Sheliugu, RA), and Coix lacryma-jobi var. ma-yuen (Rom.Caill.) Stapf (Yiyiren, CL). QYHJ has been reported to exhibit clinical efficacy in the treatment of pancreatic adenocarcinoma (PAAD). However, the molecular mechanism remains unclear. Aim of the study: This study explores the therapeutic mechanism of QYHJ in the treatment of PAAD using network pharmacology to identify related targets and pathways in vivo and in vitro . Materials and methods: The bioactive compounds of QYHJ were retrieved and screened using the ADME network pharmacology approach, followed by compound-target prediction and overlapping genes between PAAD oncogenes and QYHJ target genes. The compound-target-pathway network was established using The KEGG pathway, GO analysis, and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) analysis to identify potential action pathways. The effects of QYHJ on PAAD were evaluated in vivo and in vitro, and the predicted targets and potential pathways related to QYHJ in PAAD treatment were evaluated using qRT-PCR and immunoblotting. Results: A total of 68 bioactive compounds of QYHJ fulfilled the ADME screening criterion, and their respective 242 target genes were retrieved. The compound-target-disease network identified 11 possible target genes. The KEGG pathway analysis showed significant enrichment of pathways in cancers, involving regulating cancer-related pathways of inflammation, oxidative stress, and apoptosis. Furthermore, QYHJ inhibited PAAD growth in vivo ; suppressed cell proliferation, invasion, and migration of PAAD; and induced cellular apoptosis in vitro . The qRT-PCR results showed that QYHJ suppressed the mRNA expression of ICAM1, VCAM1, and Bcl2, and increased that of HMOX1 and NQO1. Immunoblotting revealed changes in the PI3K/AKT/mTOR, Keap1/Nrf2/HO-1/NQO1, and Bcl2/Bax pathways upon QYHJ treatment. Conclusions: QYHJ can suppress PAAD growth and progression through various mechanisms, including anti-inflammation and apoptosis-induction. Graphical abstract: Image 1 Highlights: The Qingyihuaji decoction can suppress the development and progression of pancreatic cancer in vivo and in vitro. The Qingyihuaji decoction may affect inflammation, oxidative stress, and apoptosis of pancreatic cancer. The Qingyihuaji decoction regulated the PI3K/AKT/mTOR, Keap1/Nrf2/HO-1/NQO1, and Bcl2/Bax pathways in pancreatic cancer cells.